Hypertensive crisis in the elderly: epidemiological, clinical and outcome: EDEN-47 study - Òscar Miró; Ana García-Martínez; Sira Aguiló; John Parissis; Effie Polyzogopoulou; Pere Llorens; Juan González del Castillo (Gerontology, 2026)
PURPOSE: To define the frequency and annual rate of hypertensive crisis in older patients attending emergency department (ED), the sociodemographic and baseline patient profile, and clinical characteristics and long-term outcome of the hypertensive crisis episode. We also looked for differences between men and women. METHODS: This was a retrospective analysis of the multipurpose EDEN cohort, which recruited during 1-week period all patients aged 65 years who visited the ED of 52 Spanish public hospitals covering 19.3% of Spanish population. Demographic, social, baseline and clinical data of the episode of hypertensive crisis were recorded. Estimations of annual incidence were made, in general and through patient age. Outcome consisted of 1-year post-discharge combined adverse event (revisit to ED, hospitalization, or death). Comparison between men and women were performed in unadjusted and adjusted models. RESULTS: There were 186 cases of hypertensive crises among the 25,557 patients included in the EDEN cohort. The relative frequency of hypertensive crisis was 0.73% of ED visits (95%CI 0.63-0.84), with 0.56% (0.44-0.72) in men and 0.87% (0.73-1.04) in women (OR for men 0.64, 0.47-0.87), and annual rate of hypertensive crisis in Spanish older population was 429 cases per 100.000 inhabitants (95%CI 371-493), with 341 (267-436) in men and 493 (413-590) in women (OR for men 0.69, 0.51-0.94). Patients with hypertensive crisis had better baseline health status than the rest of the older patients attending the ED, with cardiovascular comorbidity being frequent (previously known hypertension in 88.2%) and with 22% having additional acute diagnoses on top of the hypertensive crisis. Hospitalization was needed in 7.5% of cases (0.5% in intensive care unit) and in-hospital mortality was observed in 2 cases (1.1%). Combined adverse events 1 year after discharge accounted for 57.9% of patients, with 65.6% in men and 52.5% in women (adjusted HR 1.61, 1.01-2.57). CONCLUSIONS: Hypertensive crises are more frequent in older women than men and they present a worse profile at baseline and higher severity than men. Nonetheless, men with hypertensive crisis may have a worse long-term prognosis compared to women, highlighting the need for targeted post-discharge monitoring strategies in this subgroup.